In search of congruence between confessional theology and church polity discourse : a church judicial inquiry in light of the reception of the Belhar Confession in the Dutch Reformed family of churches - Pekeur, Andre Herman (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.